Análise da injeção de gás natural veicular em motores de ignição por compressão com uso de biodiesel em diferentes proporções - Gouveia, Filipe Rocha (2016)
In search for greater energy efficiency there is the application of new technologies and renewable fuels. Due to the expected shortage of oil coupled with environmental awareness, has high potential research for new energy sources and more efficient combustion processes and less polluting. Among the less polluting fuels is natural gas that has an increased consumption year on year. This paper analyzes the injection of compressed natural gas (CNG) in an internal combustion engine compression ignition, evaluating the pollutant emissions, opacity and performance. The engine under study, the energy comes from the combustion of natural gas and biodiesel, where biodiesel serves to ignite the natural gas, being possible to replace up to 80% of biodiesel injection. Thus, there is a partial substitution of biodiesel natural gas in order to increase the combustion efficiency. Engine MWM 4:07 TEC has developed an electronic injection system adapted to reduce the biodiesel injection time per cycle and compensate with CNG injection. Based on a survey of injected cycle mass flow to calculate the energy value equivalent to reducing biodiesel injection proportions to compensate with CNG injection. There was a reduction in the torque according to the increase of the proportion of biodiesel in the diesel fuel and a higher specific consumption with the use of B7 fuel (7% biodiesel). It has been found the need for injection of a larger amount of mass CNG instead of B7 fuel. Regarding the emission of pollutants in the exhaust measured at a range of engine working speed smaller carbon monoxide level (CO), carbon dioxide (CO2), hydrocarbons (HC), nitrogen oxides (NOx) were checked respectively in the application of B7 fuels, B20, B50 and B50. The lowest levels of opacity were investigated in tests using the B10 fuel.